Methods for studying the metabolic basis of Drosophila development. (26th May 2017) - Li, Hongde; Tennessen, Jason M.
Abstract : The field of metabolic research has experienced an unexpected renaissance. While this renewed interest in metabolism largely originated in response to the global increase in diabetes and obesity, studies of metabolic regulation now represent the frontier of many biomedical fields. This trend is especially apparent in developmental biology, where metabolism influences processes ranging from stem cell differentiation and tissue growth to sexual maturation and reproduction. In this regard, the fruit fly Drosophila melanogaster has emerged as a powerful tool for dissecting conserved mechanisms that underlie developmental metabolism, often with a level of detail that is simply not possible in other animals. Here we describe why the fly is an ideal system for exploring the relationship between metabolism and development, and outline a basic experimental strategy for conducting these studies. WIREs Dev Biol 2017, 6:e280. doi: 10.1002/wdev.280 This article is categorized under: Technologies > Analysis of Cell, Tissue, and Animal Phenotypes Abstract : Drosophila development progresses through four easily recognized life stages. Metabolism adapts to the energetic and biosynthetic demands of each developmental stage. Several methods are available for studying developmental metabolism in Drosophila.